Assessing the effects of calculated inaction on national responses to the COVID‐19 crisis. Issue 3 (9th June 2021) - Zahariadis, Nikolaos; Ceccoli, Stephen; Petridou, Evangelia
Abstract: How does calculated inaction affect subsequent responses to the COVID‐19 crisis? We argue that when governments employ calculated inaction during crises, they are more likely to manipulate the technical (scientific) aspects of national responses and highlight symbolic politics, each in the name of projecting power and strengthening the regime's governing authority. Using theoretical insight from McConnell and 't Hart's policy inaction typology, we investigate sense‐making and crisis response narratives in China and Greece. We conclude with implications for policymaking and the crisis management literature. 摘要: 有意不作为（calculated inaction）如何影响新冠肺炎（COVID‐19）危机响应？我们主张，当政府在危机期间有意不作为，则更有可能操纵国家响应的技术（科学）层面并强调象征性政治，二者反映了权力、加强了政权的治理权威。通过使用McConnell 和't Hart's的政策不作为分类学，我们研究了意义建构和中国和希腊的危机响应叙事。我们的结论为决策和危机管理文献提供了意义。 Resumen: ¿Cómo afecta la inacción calculada las respuestas posteriores a la crisis del COVID‐19? Argumentamos que cuando los gobiernos emplean una inacción calculada durante las crisis, es más probable que manipulen los aspectos técnicos (científicos) de las respuestas nacionales y resalten la política simbólica, cada una en nombre de proyectar poder y fortalecer la autoridad gobernante del régimen. Utilizando los conocimientos teóricos de McConnell y la tipología de inacción política de 't Hart, investigamos las narrativas de respuesta a crisis y de toma de sentido en China y Grecia. Concluimos con las implicaciones para la formulación de políticas y la literatura sobre gestión de crisis.